Artificial Intelligence between Innovation Imperatives and Regulatory Controls: An Analytical Study in Digital Content Management - Mohammed Hassan Kahat (International Journal of Law Research and Studies, 2026)
This research handles legal and regulatory challenges arising from artificial intelligence integration. The main problem is the tension between technological innovation and fundamental rights. The research objects to illustrate multidimensional implications, focusing on legislative gaps, algorithmic bias, and digital content management. It adopts a comparative analytical approach. The originality of this research lies in its highlight on the Iraqi and Arab realities as a model for developing countries facing the global digital divide. Whereas proposing accountability structures that cover the entire artificial intelligence system life cycle. The research proves that ensuring democratic control requires building effective legislative and regulatory frameworks.